Electron Transport Layer‐Free Solar Cells Based on Perovskite–Fullerene Blend Films with Enhanced Performance and Stability. Issue 18 (24th August 2016) - Pascual, Jorge; Kosta, Ivet; Tuyen Ngo, T.; Chuvilin, Andrey; Cabanero, German; Grande, Hans J.; Barea, Eva M.; Mora‐Seró, Iván; Delgado, Juan Luis; Tena‐Zaera, Ramon
Abstract: The solution processing of pinhole‐free methylammonium lead triiodide perovskite–C70 fullerene (MAPbI3 :C70 ) blend films on fluorine‐doped tin oxide (FTO)‐coated glass substrates is presented. Based on this approach, a simplified and robust protocol for the preparation of efficient electron‐transport layer (ETL)‐free perovskite solar cells is described. Power conversion efficiency (PCE) of 13.6 % under AM 1.5 G simulated sunlight is demonstrated for these devices. Comparative impedance spectroscopy and photostability analysis of the MAPbI3 :C70 and single MAPbI3 films compared with conventional compact TiO2 ETL‐based devices are shown. The beneficial impact of using MAPbI3 :C70 blend films is emphasized. Abstract : Mix, spin, go ! Perovskite solar cells based on pinhole‐free perovskite–C70 fullerene blend films deposited on fluorine‐doped tin oxide (FTO)‐coated glass substrates, without a specific electron‐transporting/blocking layer, are fabricated and characterized. Enhanced photovoltaic performance and stability with respect to traditional compact TiO2 ‐based cells is achieved for these simplified devices under continuous AM 1.5 G simulated sunlight, without the need for encapsulation.